Um estudo de caso sobre a formação de professores que ministram disciplinas a distância - Silva, Juliano Corrêa da (2014)
This master's thesis addresses a case study on the education of professors who teach higher education distance courses at a Community Higher Education Institution in Greater Metropolitan Porto Alegre. This thesis belongs to the line of research Professor Education, Educational Theories and Practices of the Graduate Program in Education at the La Salle University Center (UNILASALLE). This thesis employs the concept of the online professor, which is defined by Paloff and Pratt (2004) as the professor who cumulatively comprises the roles of professor and tutor to perform within Distance Education. The general objective of this investigation is to identify how professor education takes place online to teach in courses provided through the mixed modality via Distance Education, within on-campus higher education programs of the Higher Education Institution in focus. To this end, authors such as: Paloff and Pratt, Gauthier et al., Nóvoa, Josso, Tardif, Lévy, Freire, Zabala, Contreras, Pimenta, Mercado et al., among others, form the foundation of this study. A qualitative methodological approach with an exploratory objective was used, using the technical procedure of the case study. The data collection instrument was a questionnaire applied to online professors teaching in on-campus higher education programs in distance courses. The data were analyzed according to the textual discourse analysis proposed by Moraes and Galiazzi. The results evidence that the education of professors who taught distance courses in the Community Higher Education Institution in question in Greater Metropolitan Porto Alegre is primarily carried out through continuing education, not considering in the initial education all essential elements for performing as an online professor in DE.